Gold nanoparticles supported on reduced graphene oxide as green catalyst for solventless hydrosilylation process - Amir, Muhammad Nur Iman; Muhd Julkapli, Nurhidayatullaili; Ma'amor, Azman (Malaysian NANO-An International Journal, 2023)
The hydrosilylation reaction is a versatile process that is used to synthesize a variety of organosilicon compounds. However, the traditional metal oxide catalysts used for this reaction suffer from low activity and selectivity. In this study, we synthesized and characterized a gold nanoparticles (AuNPs)-reduced graphene oxide (rGO) catalyst for the hydrosilylation reaction. The AuNPs-rGO catalyst was synthesized by a one-pot method using trisodium citrate (Na3C6H5O7) as a reducing and capping agent. The catalyst was characterized by XRD, FESEM, and FTIR. The hydrosilylation reaction was carried out under solventless conditions using dimethylphenylsilane as the substrate. The AuNPs-rGO catalyst was found to be highly active and selective for the hydrosilylation reaction, yielding a 100% conversion of the substrate to disiloxane in 3 hours. The results of this study demonstrate the potential of AuNPs-rGO catalysts for the hydrosilylation reaction and suggest that they could be used to develop more efficient and sustainable processes for the synthesis of organosilicon compounds.